(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
Preschool education plays a pivotal role in laying the foundation for a child’s cognitive, social, and emotional development. Understanding the principles of psychology can greatly enhance the effectiveness of teaching methods employed in preschool settings. In this article, we will delve into the key psychological factors influencing preschool children and explore how educators can leverage this knowledge to create a stimulating and supportive learning environment.